Designing a Farsi text for the assessment of adult voice features and determining its validity and reliability in measuring the fundamental frequency and intensity of speech - Asefeh Memarian; Ali Ghorbani; Farhad Torabi Nejad; Mohammad Reza Keyhani (Vesnu Publications, 2010)
<!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:"B Zar"; panose-1:0 0 4 0 0 0 0 0 0 0; mso-font-charset:178; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:8193 -2147483648 8 0 64 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:AR-SA;} p.abst, li.abst, div.abst {mso-style-name:abst; mso-style-unhide:no; margin-top:3.0pt; margin-right:0cm; margin-bottom:0cm; margin-left:0cm; margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:11.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"B Zar";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> Introduction: The every possible attempt in voice disorders assessment is to gather samples which represent individuals' actual voice in the daily speech. The researchers have found that voice characteristics in reading a passage are closer to daily speech. Making texts has been started since early 20th century. The lack of suitable text in Farsi language makes it difficult to conduct requisite researches and present documentary results of interventions. Researchers believe that Sara lip reading test which had been used for voice studies in Farsi language is not appropriate. The goal of this study is to make an appropriate text for assessing the voice characteristics which is also effective for both research and clinical goals. Materials and Methods: The required text was made by the study of the characteristics of used texts in other languages, considering the Dr. Speech software limitations in analyzing duration of stimuli and the results from investigations used Sara lip reading test. The content validity of this text was assessed. Its reliability was determined by test-retest method. Results: The content validity of the text was confirmed by the university professors. In examining the reliability, it was indicated that measuring the studied characteristics has a high reliability.   Conclusion: There was a general consensus among university professors about the text validity. In examining the reliability, Cronbach's alpha was more than 0.7 in studied variables. Considering the confirmed validity and reliability, it can be concluded that this text can be used for assessing voice characteristics in voice studies in normal samples